2011
DOI: 10.1038/labinvest.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free imidazolium salts inhibit the growth of hepatocellular carcinoma in a mouse model

Abstract: Imidazolium salts (IMSs) are precursors to N-heterocyclic carbenes (NHCs), which are routinely used as ligands or organocatalysts in synthetic chemistry. We recently identified several IMSs as anti-fibrotic agents in liver fibrosis, which often has a consequence in the oncogenesis of hepatocellular carcinoma (HCC). Here, we investigate the potential anti-tumor property of three IMSs (named IBN-1, IBN-9, and DPIM) in HCC cell lines and in a xenograft mouse model. Our results showed that both IBN-1 and IBN-9 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…More recently, the first animal model to study the antitumor properties of selected imidazolium salts was reported by Zhuo's group. 22 Three imidazolium salts 15-17 were selected in their study, Scheme 8. The antitumor properties of these three IMSs were investigated in hepatocellular carcinoma (HCC) cell lines, and in a xenograft mouse model.…”
Section: Antitumor Activity Of Imidazolium Saltsmentioning
confidence: 99%
“…More recently, the first animal model to study the antitumor properties of selected imidazolium salts was reported by Zhuo's group. 22 Three imidazolium salts 15-17 were selected in their study, Scheme 8. The antitumor properties of these three IMSs were investigated in hepatocellular carcinoma (HCC) cell lines, and in a xenograft mouse model.…”
Section: Antitumor Activity Of Imidazolium Saltsmentioning
confidence: 99%
“…2,2=-Bipyridine 3 was obtained from Joachim W. Heinicke, Ernst Moritz Arndt University of Greifswald, Greifswald, Germany. The cytotoxic lipophilic imidazolium salt 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride 3 was synthesized as described previously (54)(55)(56). The arylimidamide DB745 2 (23) was kindly provided by David Boykin, Georgia State University, Atlanta, GA.…”
mentioning
confidence: 99%
“…Several reports have shown that imidazolium salts possess promising anticancer activities [13,16,[32][33][34][35][36][37][38][39][40][41]. We evaluated the anticancer activities of lithocholic acid-based imidazolium salts (S1-S10) against three different colorectal cancer cell lines (DLD-1, HT-29, and Caco-2).…”
Section: Imidazolium Salts Decrease Colon Cancer Viability and Metabo...mentioning
confidence: 99%